Effects of different soil amendments on soil physical and chemical properties and oil sunflower yield in saline-sodic in Northern Shaanxi China (Bangladesh Journal of Botany, 2025)
In order to explore the response effects of different amendments and salt tolerant crops on the management of moderate saline-sodic and crop yield, this study was carried out in typical saline-sodic in Northern Shaanxi. Taking the salt tolerant crop oil sunflower as the research object, three soil amendments were applied, including desulfurization gypsum (FGD), "xiyoufeng" soil amendment (SA) and "yueyuyuan" microbial agent (MA). The effects of different amendments on soil physical and chemical properties and oil sunflower yield were analyzed. The results showed that the application of soil additives effectively reduced the soil pH, total salt content and bulk density of saline-sodic by 2.24~10.15, 0.82~15.76 and 2.67%~8.00%; the soil organic matter, hydrolyzable nitrogen, available phosphorus and available potassium were increased respectively by 15.65~56.55, 2.32~39.57, 49.75~95.48 and 5.33%~32.96%; the plant height and stem diameter of oil sunflower were increased respectively by 1.50~9.02%, 0.84~4.20%; the yield was increased by 17.67~72.24%, and the quality was improved. Compared with CK, soil pH, total salt content and bulk density decreased by 0.91, 0.12 g/kg and 0.84 g/cm3, respectively, and the yield increased by 1153.37   kg/hm-2, which provided a practical reference scheme for the improvement of saline-sodic in arid areas. It was suggested that YUEYUYUAN microbial agent should be preferred to treat moderate saline-sodic in Northern Shaanxi. Our study provides scientific recommendations for applying amendments worldwide in the saline-sodic.Bangladesh J. Bot. 54(3): 769-781, 2025 (September) Special